Clostridium difficile – an Important Opportunistic Pathogen in Healthcare-Associated Infections - Soohyoun Ahn; Amarat H. Simonne (EDIS)
Opportunistic pathogens are significant health threats to vulnerable people with weakened immune systems, such as people with HIV/AIDS or those on immune-suppressing therapies. One opportunistic pathogen, Clostridium difficile, has been getting more attention in recent years because of its association with antibiotic use and high death rate in the elderly. This factsheet will provide an overview of Clostridium difficile infection (CDI) with a focus on healthcare-associated infections. This 5-page fact sheet was written by Soohyoun Ahn and Amarat H. Simonne, and published by the UF Department of Food Science and Human Nutrition, September 2014.